2013
DOI: 10.1111/ctr.12150
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of sorafenib for the treatment of recurrent hepatocellular carcinoma after liver transplantation

Abstract: Sorafenib can be well tolerated and safe in patients with recurrent HCC following LT and may be associated with a modest survival benefit. To our knowledge, this is the largest single-center retrospective analysis of patients prescribed sorafenib for recurrent HCC after LT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 24 publications
1
38
0
1
Order By: Relevance
“…Two independent randomized Phase III clinical trials showed that sorafenib was the only effective systemic drug to improve survival in patients with advanced HCC (14,15). Furthermore, sorafenib is reported to be well tolerated and safe in patients who received liver transplantation and is associated with a survival benefit (16)(17)(18). In a randomised controlled phase III clinical trial (STORM), sorafenib was administrated to patients with a medianhigh risk of recurrence, the clinical trial is still ongoing and waiting for final results (19).…”
Section: Introductionmentioning
confidence: 99%
“…Two independent randomized Phase III clinical trials showed that sorafenib was the only effective systemic drug to improve survival in patients with advanced HCC (14,15). Furthermore, sorafenib is reported to be well tolerated and safe in patients who received liver transplantation and is associated with a survival benefit (16)(17)(18). In a randomised controlled phase III clinical trial (STORM), sorafenib was administrated to patients with a medianhigh risk of recurrence, the clinical trial is still ongoing and waiting for final results (19).…”
Section: Introductionmentioning
confidence: 99%
“…The case is especial for SORA and EVL-resistance HCC. Although SORA and EVL are generally recommended sequentially or co-instantaneously, there is still lack of optimal treatment modality [2][3][4]6]. No alternative drug or treatment had shown an obvious survival benefit in HCC with SORA or EVLresistant after transplant [11].…”
Section: Discussionmentioning
confidence: 99%
“…Compared to various therapeutic approaches used before recurrence, including local treatment, hepatic resection and chemotherapy, no standard posttransplant adjuvant chemotherapy has been established. Sorafinib (SORA) and everolimus (EVL) have already been investigated for application in recurrence HCC after LT [3][4][5][6] based on roles of B-Raf and mammalian target of rapamycin (mTOR)/protein kinase B (AKT) pathways in the pathogenesis of HCC [7,8]. Targeted next generation sequencing (NGS) of tumor samples can provide molecular abnormalities of different pathways for prediction of treatment outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Two large randomized control trials have demonstrated that it can increase survival of patients with advanced HCC by approximately 2 to 3 months, and the Food and Drug Administration approved it in 2007 for this patient population [12, 13]. Recent case-control studies have demonstrated similar modest survival benefit in patients with recurrent HCC following liver transplantation [14, 15], and based on current data, algorithms that integrate sorafenib into the management of posttransplant HCC recurrence are emerging [16]. …”
Section: Discussionmentioning
confidence: 99%